Development of a Standardized Model for Liver Failure in Pigs: Anatomopathophysiologic Findings After Extended Liver Resection (2012)
Eighteen pigs weighing a mean 19 ± 4 kg, were divided into group 1 (n = 2), that underwent resection of the left lateral lobe, group 2 (n = 2), resection of the left median and right median lobes; and group 3 (n = 18), resection of the left lateral, left median, right median, and right lateral lobes. All animals were followed for 5 days. Liver failure (n = 8) leading to animal death within 3 days after surgery was observed in 65% of group 3, whereas no group 1 or 2 animal experienced liver insufficiency. Multivariate analysis revealed that the extent of liver resection expressed as a percentage of total body weight <2.3%, international normalized ratio > 1.6 as postoperative day 2, serum bilirubin > 4.2 on postoperative day 2, and serum lactates > 9 mmol/L after resection were independent predictors of liver failure (P < .05). The number of resected liver lobes was not a good predictor of liver failure in swine, whereas the extent of resection expressed as a percentage of total body weight was an independent predictor of early liver failure. A resected liver-to-body weight ratio >2.3% was associated with a 65% probability of developing liver insufficiency. This parameter may be useful when developing a model of liver failure after extended liver resection in swine.